2002
DOI: 10.1677/joe.0.1720387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oestrogen deprivation on interleukin-6 production by peripheral blood mononuclear cells of postmenopausal women

Abstract: Various hormones can influence the expression of interleukin-6 (IL-6) and oestrogens are the most extensively studied. There is, however, controversy about the nature of the IL-6 secreted by human cells and its regulation by 17 -oestradiol. The aim of this work was to clarify whether oestrogen deprivation after menopause may contribute to an enhanced IL-6 production by peripheral blood mononuclear cells (PBMC) in postmenopausal women. Twenty-two healthy postmenopausal women, age range 45-63 years, with clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 52 publications
4
49
2
2
Order By: Relevance
“…This result might reflect a loss in the regulatory effect of estrogen on PBMC cytokine production in postmenopausal women. This is consistent with the finding of Rachoń et al (2002), who determined that women with non-stimulated PBMCs that express IL-6 have significantly lower serum levels of estradiol, as compared to women with PBMCs that do not express IL-6. It has also been suggested that increased cytokine production in healthy, older individuals result from reduced levels of sex hormones (Ershler and Keller 2000).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This result might reflect a loss in the regulatory effect of estrogen on PBMC cytokine production in postmenopausal women. This is consistent with the finding of Rachoń et al (2002), who determined that women with non-stimulated PBMCs that express IL-6 have significantly lower serum levels of estradiol, as compared to women with PBMCs that do not express IL-6. It has also been suggested that increased cytokine production in healthy, older individuals result from reduced levels of sex hormones (Ershler and Keller 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Postmenopausal status (n=94) was defined as an absence of menstruation for at least 12 months and the presence of estrogen deficiency symptoms including "hot flushes," increased sweating, nervousness, irritability, depression, palpitations, insomnia, headaches, dyspareunia, and joint pains. The cessation of ovarian function was confirmed by measurement of serum levels of follicle-stimulating hormone (FSH), which should be above 40 IU/L if loss of ovarian function has occurred (Rachoń et al 2002). Premenopausal status (n=114) was defined as the presence of regular menses (Rachoń et al 2002).…”
Section: Participants and Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…After the separation, a thin layer of PBMCs was isolated and washed twice with RPMI 1640. The pellet was resuspended in RPMI 1640 supplemented with 10% fetal bovine serum (Gibco, Invitrogen) and seeded in 12-well plates (1 × 106 cells/ml; Nunc, Roskilde, Denmark) and incubated at 37°C with 5% CO 2 for 24 h. After 24 h incubation, supernatants were collected and stored at 80°C until interleukin (IL)-1 ␤ , IL-6, TNF-␣ , and Lp-PLA 2 activity levels were assayed ( 13,14 ).…”
Section: Cytokine Secretion In Nonstimulated Pbmcsmentioning
confidence: 99%